Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian (Studi Pada Ina Cookies Bandung) - Fiera Aryati Natakusumah; Ai Lili Yuliati (Universitas Airlangga, 2016)
This research is motivated by the problems related to the marketing mix Ina Cookies. Those problems based on the results of the initial interview is indicative of consumer complaints related to marketing mix consisting of product, price, place and promotion. This study aims to determine the effect of marketing mix consisting of product, price, place and promotion on purchase decisions.The method used is quantitative method with descriptive research and causal. Source data using primary and secondary data, sampling techniques using Non Probability sampling with incidental sampling with the number of respondents as many as 400 people. Data were analyzed using descriptive analysis and multiple linear regression analysis.The results showed that the mix of marketing and consumer purchase decisions on Ina Cookies included in either category. The marketing mix consists of product, price, place and promotion simultaneously or partially positive and significant impact on purchasing decisions.